Composite solid waste synergetic soil roadbed filler as well as preparation method and application thereof
By using composite solid waste collaborative soil technology in roadbed fillers, combined with coarse-grained soil, waste clay brick recycled powder and circulating fluidized bed solid sulfur ash, the problems of high cost and insufficient compressive strength caused by high CFB solid sulfur ash blending rate are solved, and efficient and economical preparation of roadbed fillers is achieved, which improves the mechanical properties and service life of highway roadbeds.
Patent Information
- Application Number
- CN202411787837.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-11
AI Technical Summary
At this stage, there are few reports of circulating fluidized bed solid sulfur ash (CFB solid sulfur ash) used for roadbed fillers, and the high CFB solid sulfur ash blending rate leads to high roadbed filling time and price cost, affecting the construction progress, and affecting the compressive strength of the fillers, resulting in insufficient service life of highway roadbeds.
A composite solid waste coordinated soil subgrade filler is used, and its raw materials include coarse-grained soil, waste clay brick recycled powder and circulating fluidized bed solid sulfur ash. Through coordinated modification, its hydration reaction strength is significantly improved, forming a dense honeycomb gel network structure to enhance mechanical properties.
It effectively enhances the compressive strength, rebound modulus and compressibility of the roadbed filler, improves the shear strength, reduces the price and time cost, and ensures the high load-bearing capacity and service life of the roadbed.
Smart Images

Figure CN119591356A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of solid waste utilization and road filling subgrade, and in particular relates to a composite solid waste coordinated soil subgrade filler and a preparation method and application thereof. Background Art
[0002] The roadbed is the supporting carrier of the pavement structure, and its bearing capacity has a great impact on the safety and life of the road. At present, in order to design a roadbed that meets the bearing capacity requirements, it is usually required to fill the roadbed with high compressive strength to resist the traffic load, so as to ensure that the roadbed will not settle and deform. Therefore, the design and preparation of roadbed fillers with suitable compressive strength has become a research hotspot.
[0003] Circulating fluidized bed sulfur-fixing ash (CFB sulfur-fixing ash) is a solid waste produced by burning low calorific value fuels such as coal powder, coal gangue, coal mud and sulfur-fixing agent through circulating fluidized bed technology. Its chemical composition (high content of f-CaO and SO3 in the ash) is different from ordinary fly ash, which makes CFB sulfur-fixing ash self-hardening, expansive and high water demand. In particular, the expansiveness restricts its resource recycling in building materials. At present, in order to solve the problem of limited resource recycling of CFB sulfur-fixing ash in building materials, domestic and foreign research uses CFB sulfur-fixing ash as roadbed filler, and fills the roadbed in the form of "ash instead of soil" to achieve efficient resource utilization of CFB sulfur-fixing ash.
[0004] However, at present, there are few reports on the use of CFB sulfur-fixing ash as roadbed filling material, and related research generally focuses on "single CFB sulfur-fixing ash full replacement of soil" or "single CFB sulfur-fixing ash high proportion blended soil". The higher usage of CFB sulfur-fixing ash leads to high roadbed filling time and price costs, affecting the progress of roadbed construction. In addition, the high CFB sulfur-fixing ash blending rate can easily increase the water storage capacity of the filler, thereby affecting the compressive strength of the filler, resulting in insufficient service life of the highway roadbed. Summary of the invention
[0005] The present application discloses a composite solid waste cooperative soil roadbed filler and a preparation method and application thereof, which effectively solve the technical problems that the high CFB solid sulfur ash admixture amount affects the roadbed compressive strength and the high cost.
[0006] In order to achieve the above objectives, the technical solution adopted in this application is:
[0007] The first aspect of the present application provides a composite solid waste and soil roadbed filler, the raw materials of which include:
[0008] Coarse-grained soil 60wt%;
[0009] 8-15wt% recycled powder from waste clay bricks; and
[0010] Circulating fluidized bed sulfur-fixing ash 25-32wt%.
[0011] According to the roadbed filler disclosed in this application, its raw materials include:
[0012] 60wt% coarse-grained soil, 8wt% recycled powder from discarded clay bricks and 32wt% circulating fluidized bed sulfur-fixing ash;
[0013] or,
[0014] 60wt% coarse-grained soil, 10wt% recycled powder from discarded clay bricks and 30wt% circulating fluidized bed sulfur-fixing ash;
[0015] or,
[0016] 60wt% of coarse-grained soil, 13.3wt% of recycled powder from discarded clay bricks and 26.7wt% of circulating fluidized bed sulfur-fixing ash.
[0017] According to the roadbed filler disclosed in the present application, the chemical composition of the waste clay brick recycled powder preferably includes SiO2, CaO and Al2O3, and the sum of the masses of the SiO2, CaO and Al2O3 is 84.35% and above of its entire chemical composition.
[0018] According to the roadbed filler disclosed in the present application, the average particle size of the waste clay brick recycled powder is 17.74 μm.
[0019] According to the roadbed filler disclosed in the present application, the chemical composition of the circulating fluidized bed sulfur-fixing ash includes SiO2, CaO and Al2O3, and the sum of the masses of the SiO2, CaO and Al2O3 is 83.89% and above of all its chemical compositions, and the mass of the CaO is 10% and above of all its chemical compositions.
[0020] According to the roadbed filler disclosed in the present application, the average particle size of the circulating fluidized bed sulfur-fixing ash is 15.67 μm.
[0021] The second aspect of the present application provides a method for preparing the composite solid waste and soil roadbed filler of the present application, the steps of which include:
[0022] The step of mixing the raw material components;
[0023] and, adding water to the mixture obtained in the previous step and sealing and placing the mixture.
[0024] According to the preparation method disclosed in the present application, the amount of water added to the mixture is 16.3-21.3% of its weight.
[0025] The third aspect of the present application provides the application of the composite solid waste of the present application in conjunction with soil roadbed filling material in the backfill construction of roadbed earth.
[0026] According to the application disclosed in the present application, during the backfill construction, the compaction degree is 96-98%.
[0027] Compared with the prior art, the advantages or beneficial effects of the present application include at least:
[0028] The roadbed filler provided by the present application is modified by coarse-grained soil with circulating fluidized bed solid sulfur ash and waste clay brick regeneration powder, wherein the circulating fluidized bed solid sulfur ash and waste clay brick regeneration powder can stimulate each other's volcanic ash activity and produce synergy, so that the hydration reaction intensity of both is significantly improved, thereby producing more gel phase products and hydration products that can support strength, which not only effectively enhances the cementation and locking effect between the solidified soil particles and changes the density of the cementation structure, so that the solidified soil has high bearing capacity, rebound modulus and compressibility, but also the circulating fluidized bed solid sulfur ash and waste clay brick powder synergistically can form a dense honeycomb gel network structure, effectively limit the relative sliding of the solidified soil particles, and effectively improve the shear strength of the solidified soil, thereby giving the prepared roadbed filler excellent mechanical properties through the synergistic effect between the components contained. In addition, the roadbed filler of the present application scientifically controls the synergistic ratio of the circulating fluidized bed solid sulfur ash and the waste clay brick regeneration powder and the amount of the solid waste system in the coarse-grained soil, thereby meeting the requirements of highway mechanical properties while ensuring a low price and time cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments recorded in the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0030] Figure 1 The changes in the compression coefficient and compression modulus of the test pieces BF1-BF4 provided in the embodiments of the present application;
[0031] Figure 2 A curve diagram showing the change of water loss rate and shrinkage strain of the specimens BF1-BF4 provided in the embodiments of the present application with the curing age;
[0032] Figure 3 XRD diagrams of mineral phases of hydration products of waste clay brick recycled powder and circulating fluidized bed sulfur-fixing ash synergistic slurry test blocks at 3d and 28d ages, respectively, provided in the examples of the present application;
[0033] Figure 4 Microscopic morphology of the waste clay brick recycled powder and circulating fluidized bed sulfur-fixing ash synergistic slurry test blocks provided in the examples of the present application after hydration for 3d and 28d respectively. DETAILED DESCRIPTION
[0034] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0035] In the following description of this specification, the term "and / or" is used to describe the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, B exists alone, and A and B exist at the same time. Among them, A and B can be singular or plural; the symbol " / " means "or".
[0036] In the following description of this specification, the term "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single or plural items. For example, "at least one of A, B or C", or "at least one of A, B and C" can mean any one of A, B, C, or A+B, or A+C, or B+C, or A+B+C, where A, B, C can be single or multiple, respectively.
[0037] In the following description of this specification, the order of serial numbers does not mean the order of execution. Some or all of the steps can be executed in parallel or one after the other. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of this embodiment.
[0038] In the following description of this specification, the numerical range should be understood to also specifically disclose each intermediate value between the upper and lower limits of the range. Any stated value or intermediate value in the stated range and any other stated value or each smaller range between the intermediate values in the range are also included in this embodiment, and the upper and lower limits of the smaller range can be independently included or excluded in the range.
[0039] Unless otherwise specified, the technical / scientific terms used in this specification have the meanings commonly understood by those skilled in the art. Although this specification only describes preferred materials and methods, any similar or equivalent methods and materials may also be used in specific embodiments or test cases. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0040] In a first aspect, the embodiment of the present application provides a composite solid waste and soil roadbed filler. The raw materials of the composite solid waste and soil roadbed filler of the embodiment of the present application include:
[0041] Coarse-grained soil 60wt%;
[0042] 8-15wt% recycled powder from waste clay bricks; and
[0043] Circulating fluidized bed sulfur-fixing ash 25-32wt%.
[0044] It should be noted that the coarse-grained soil is the main body of the filler and can be obtained from the construction site according to demand. For example, the example of this application was taken from Wugong County, Xianyang City, Shaanxi Province, and its chemical composition and physical properties are shown in Table 1-1 and Table 1-2 respectively.
[0045] Table 1-1: Chemical composition of coarse-grained soil (wt%)
[0046]
[0047] Table 1-2: Physical properties of coarse-grained soil
[0048]
[0049] It should be noted that the waste clay brick regeneration powder and circulating fluidized bed sulfur fixation ash are used to synergistically modify the coarse-grained soil, and its chemical composition is shown in Table 2. Among them, the waste clay brick regeneration powder refers to the recycled powder obtained by grinding the waste clay bricks in a ball mill. The embodiment of this application is preferably taken from Shanxi Xiyuefa Company. The main mineral phases are quartz (SiO2), lime (CaO) and albite (Na2O·Al2O3·6SiO2), with an average particle size of 17.74μm and a specific surface area of 501cm 2 ·g -1 The circulating fluidized bed sulfur-fixing ash is preferably taken from the Huadian Yaochi Thermal Power Plant in Bin County, Shaanxi Province. Its CaO content is greater than 10%, the free calcium oxide (f-CaO) content is 1.25-4%, the ignition loss is 3.50%, and the main mineral phases are quartz (SiO2), calcium hydroxide (Ca(OH)2), mullite (3Al2O3·2SiO2) and anhydrite (CaSO4). The average particle size is 15.67μm, the surface is loose and porous, and the particles are irregular.
[0050] Table 2: Chemical composition of recycled powder from waste clay bricks and circulating fluidized bed sulfur fixation ash (wt%)
[0051]
[0052] According to Table 2, the chemical composition of the recycled powder of waste clay bricks described in the present application includes SiO2, CaO and Al2O3, and the sum of the masses of SiO2, CaO and Al2O3 is 84.35% and above of all its chemical compositions; the chemical composition of the circulating fluidized bed sulfur-fixing ash described in the present application includes SiO2, CaO and Al2O3, and the sum of the masses of SiO2, CaO and Al2O3 is 83.89% and above of all its chemical compositions, and the mass of CaO is 10% and above of all its chemical compositions.
[0053] In summary, the embodiments of the present application modify coarse-grained soil by synergistically modifying the coarse-grained soil with circulating fluidized bed sulfur-fixing ash and waste clay brick recycled powder, wherein the circulating fluidized bed sulfur-fixing ash and waste clay brick recycled powder can stimulate each other's volcanic ash activity and produce a synergistic effect, so that the hydration reaction intensity of both is significantly improved, thereby producing more gel phase products and hydration products that can support strength, which not only effectively enhances the cementation and locking effect between the solidified soil particles and changes the density of the cementation structure, so that the solidified soil has high bearing capacity, rebound modulus and compressibility, but also the circulating fluidized bed sulfur-fixing ash and waste clay brick powder can synergistically form a dense honeycomb gel network structure, effectively limit the relative sliding of the solidified soil particles, and effectively improve the shear strength of the solidified soil, thereby giving the prepared roadbed filler excellent mechanical properties through the synergistic effect between the components contained. In addition, the roadbed filler of the present application scientifically controls the synergistic ratio of circulating fluidized bed sulfur-fixing ash and waste clay brick recycled powder and the blending amount of the solid waste system in the coarse-grained soil, thereby meeting the requirements of highway mechanical properties while ensuring lower price and time costs.
[0054] In an exemplary embodiment, the composite solid waste and soil roadbed filler preferably comprises:
[0055] 60wt% coarse-grained soil, 8wt% recycled powder from discarded clay bricks and 32wt% circulating fluidized bed sulfur-fixing ash;
[0056] or,
[0057] 60wt% coarse-grained soil, 10wt% recycled powder from discarded clay bricks and 30wt% circulating fluidized bed sulfur-fixing ash;
[0058] or,
[0059] 60wt% of coarse-grained soil, 13.3wt% of recycled powder from discarded clay bricks and 26.7wt% of circulating fluidized bed sulfur-fixing ash.
[0060] Of course, the raw material content of the modified gelling material may include any combination within the optional range of the raw materials in addition to the examples described above, and this specification will not describe them one by one; at the same time, the contents described in this specification are all in mass percentage.
[0061] The present application uses the solid waste composite system of the physicochemical composition of the waste clay brick recycled powder and the circulating fluidized bed solid sulfur ash to synergistically modify and regulate the physicochemical composition of the coarse-grained soil, so as to fully stimulate the volcanic ash activity of the waste clay brick recycled powder and the circulating fluidized bed solid sulfur ash contained therein and make them produce a synergistic effect, so that the hydration reaction intensity of both is significantly improved, thereby producing more gel phase products and hydration products that can support strength, which not only effectively enhances the cementation and locking effect between the solidified soil particles and changes the density of the cementation body, so that the solidified soil structure has high bearing capacity, rebound modulus and compressibility, but also the circulating fluidized bed solid sulfur ash and the waste clay brick powder can synergistically form a dense honeycomb gel network structure, effectively restricting the relative sliding of the coarse-grained soil particles, so that the shear strength of the solidified soil structure is improved, thereby giving the roadbed filler excellent mechanical properties through the synergistic effect between the components contained.
[0062] In a second aspect, the present application provides a method for preparing the composite solid waste-solid roadbed filler as described above, preferably comprising the steps of:
[0063] The step of mixing the raw material components;
[0064] and, adding water to the mixture obtained in the previous step and sealing and placing the mixture.
[0065] In the exemplary implementation, the amount of water added to the mixture is 16.3-21.3% of its weight. In particular, by controlling the water addition rate, the embodiment of the present application can effectively ensure that the roadbed filler has a good maximum dry density, so that the waste clay brick recycled powder and circulating fluidized bed sulfur-fixing ash in the roadbed filler can fully produce a dispersed filling effect in the subsequent compaction operation, thereby increasing the adhesion between the components contained in the roadbed filler.
[0066] In the third aspect, the embodiment of the present application provides the application of the composite solid waste and soil roadbed filler described in the present application in the backfill construction of roadbed earthwork. Among them, during the backfill construction, the compaction degree is 96-98%. By controlling the compaction degree, the present application can make the waste clay brick recycled powder and circulating fluidized bed sulfur ash in the roadbed filler fully produce a dispersed filling effect in the subsequent compaction operation, effectively improving the adhesion between the components contained in the roadbed filler.
[0067] The technical solution of the present application will be further described below in conjunction with specific embodiments.
[0068] Example 1
[0069] This embodiment provides a composite solid waste and soil roadbed filler. The raw material composition of the composite solid waste and soil roadbed filler in this embodiment is:
[0070] 60 parts by mass of coarse-grained soil;
[0071] 8 parts by mass of recycled powder from waste clay bricks;
[0072] 32 parts by mass of circulating fluidized bed sulfur-fixing ash.
[0073] The composite solid waste and soil roadbed filler is prepared according to the following steps:
[0074] The coarse-grained soil, recycled powder of discarded clay bricks and circulating fluidized bed sulfur-fixing ash are stirred and mixed according to the mass fractions, and then 16.3% of water in mass of the obtained mixture is added, and the mixture is sealed and placed for 1 day to obtain the product.
[0075] Example 2
[0076] This embodiment provides a composite solid waste and soil roadbed filler. The raw material composition of the composite solid waste and soil roadbed filler in this embodiment is:
[0077] 60 parts by mass of coarse-grained soil;
[0078] 10 parts by mass of recycled powder from waste clay bricks;
[0079] 30 parts by mass of circulating fluidized bed sulfur-fixing ash.
[0080] The composite solid waste and soil roadbed filler is prepared according to the following steps:
[0081] The coarse-grained soil, recycled powder of discarded clay bricks and circulating fluidized bed sulfur-fixing ash are stirred and mixed according to the mass fractions, and then 16.3% of water in mass of the obtained mixture is added, and the mixture is sealed and placed for 1 day to obtain the product.
[0082] Example 3
[0083] This embodiment provides a composite solid waste and soil roadbed filler. The raw material composition of the composite solid waste and soil roadbed filler in this embodiment is:
[0084] 60 parts by mass of coarse-grained soil;
[0085] 13.3 parts by mass of recycled powder from waste clay bricks;
[0086] 26.7 parts by mass of circulating fluidized bed sulfur-fixing ash.
[0087] The composite solid waste and soil roadbed filler is prepared according to the following steps:
[0088] The coarse-grained soil, recycled powder of discarded clay bricks and circulating fluidized bed sulfur-fixing ash are stirred and mixed according to the mass fractions, and then 16.3% of water in mass of the obtained mixture is added, and the mixture is sealed and placed for 1 day to obtain the product.
[0089] In order to illustrate the technical effect of the composite solid waste in the present application in conjunction with soil roadbed filler, this article also provides comparative examples 1-3. Among them, comparative examples 1-2 are single-component blends of waste clay brick recycled powder or circulating fluidized bed sulfur-fixing ash, and comparative example 3 is a composite component blend of waste clay brick recycled powder and circulating fluidized bed sulfur-fixing ash, and the preparation method is the same as the above-mentioned embodiment.
[0090] According to the Chinese standards "Highway Geotechnical Test Code (JTG 3430-2020)" and "Highway Engineering Inorganic Binder Stabilized Material Test Code (JTG E51-2009)", the roadbed fillers prepared in the examples and comparative examples were prepared into test pieces and cured, and their performance was tested according to the following method. The test piece components are shown in Table 3.
[0091] Table 3: Test piece components
[0092]
[0093] 1. Mechanical properties test method
[0094] By studying the unconfined compressive strength, CBR value, shear strength, compressibility and other indicators, the raw material mix ratio of the composite solid waste and soil roadbed filler in this application is clarified.
[0095] 1.1 According to the provisions of T0148-1993 in JTG 3430-2020, a Φ50mm×50mm cylindrical specimen was prepared for testing the unconfined compressive strength;
[0096] 1.2 According to the provisions of T0134-2019 in JTG 3430-2020, a Φ150mm×120mm cylindrical specimen was prepared to measure the California load ratio;
[0097] 1.3 According to the provisions of T0135-1993 in JTG 3430-2020, a cylindrical specimen of Φ150 mm × 120 mm was prepared for measuring the rebound modulus;
[0098] 1.4 According to the provisions of T0140-2019 in JTG 3430-2020, a cylindrical specimen of Φ79.8mm×20mm was prepared to measure the shear strength;
[0099] 1.5 According to the provisions of T0137-1993 in JTG 3430-2020, a cylindrical specimen of Φ79.8 mm × 20 mm was prepared for measuring the specimens for the consolidation test;
[0100] 1.6 According to the provisions of T0854-2009 in JTG E51-2009, prepare 50mm×50mm×200mm prism specimens for measuring shrinkage properties;
[0101] Among them, vibration compaction is used to determine the optimal moisture content and maximum dry density of each specimen, and the compaction degree during the specimen molding process is 98%. The specimens are all cured under standard curing conditions (temperature 20±2℃, humidity>95%).
[0102] 2. Mechanical properties test results
[0103] 2.1 The unconfined compressive strength test results are shown in Table 4.
[0104] Table 4: Unconfined compressive strength test results
[0105] Test piece 7 days 28 days 7 days of immersion 28 days of immersion index 1.1MPa --- --- --- JZ1 0.4MPa 1.4MPa 0MPa 0MPa JZ2 0.5MPa 1.6MPa 0MPa 0MPa BF1 1.8MPa 3.7MPa 0.67MPa 1.6MPa BF2 1.9MPa 3.9MPa 0.77MPa 1.73MPa BF3 2.1MPa 4.4MPa 0.81MPa 1.77MPa BF4 2.4MPa 5.3MPa 1.47MPa 2.1MPa
[0106] According to Table 4, the unconfined compressive strength of the synergistic blended specimens of waste clay brick recycled powder and circulating fluidized bed sulfur-fixing ash is several times better than that of the single blended specimens of waste clay brick recycled powder or circulating fluidized bed sulfur-fixing ash, and the unconfined compressive strength of the synergistic blended specimens increases rapidly first and then decreases slowly as the amount of circulating fluidized bed sulfur-fixing ash increases. Specifically, the unconfined compressive strength of specimens JZ1-JZ2 at 7d and 28d after immersion in water was 0, and the unconfined compressive strength of specimens BF1-BF4 at 7d and 28d after immersion in water was greater than 0. The reason for this phenomenon may be that when waste clay brick recycled powder or circulating fluidized bed sulfur ash solidifies coarse-grained soil, physical compaction occurs inside the material (without chemical reaction), and immersion in water causes serious damage to the internal structure, resulting in an unconfined compressive strength of 0. When waste clay brick recycled powder and circulating fluidized bed sulfur ash synergistically solidify coarse-grained soil, they can stimulate each other's potential volcanic ash activity, thereby causing hydration reaction inside the mixture and forming hydration products that can enhance the mechanical strength of the mixture. In addition, the unconfined compressive strength of specimen BF4 at 7d and 28d before and after immersion in water reached the maximum, while the unconfined compressive strength of specimen BF1 at 7d and 28d before and after immersion in water was the minimum, indicating that the synergistic ratio between the two will affect the hydration reaction.
[0107] 2.2CBR value analysis is shown in Table 5.
[0108] Table 5: CBR value analysis results
[0109]
[0110] According to Table 5, the CBR values of specimens JZ1-JZ2 and BF1-BF4 both increase significantly with the increase of compaction degree, but when the compaction degree is 96-98%, the CBR value of the synergistic blending specimen of waste clay brick recycled powder and circulating fluidized bed sulfur-fixing ash is multiple times better than the CBR value of the single blending specimen of waste clay brick recycled powder or circulating fluidized bed sulfur-fixing ash, and the CBR value of the synergistic blending specimen shows a trend of first rapid increase and then slow decrease with the increase of circulating fluidized bed sulfur-fixing ash dosage. In particular, when the compaction degree is 96-98%, the CBR value of specimen BF1 is less than the sum of the CBR values of specimens JZ1-JZ2, while the CBR value of specimens BF2-BF4 is greater than the sum of the CBR values of specimens JZ1-JZ2, indicating that the synergistic blending of waste clay brick recycled powder and circulating fluidized bed sulfur-fixing ash according to the ratio of BF2-BF4 produces a synergistic effect. Therefore, the compaction degree is preferably 96-98%, and the ratio of waste clay brick recycled powder to circulating fluidized bed sulfur-fixing ash is preferably the ratio described in specimens BF2-BF4.
[0111] 2.3 The results of the rebound modulus analysis are shown in Table 6.
[0112] Table 6: Rebound modulus analysis results
[0113] Test piece JZ1 JZ2 BF1 BF2 BF3 BF4 Elastic modulus (MPa) 41.5 42.2 62 63.7 67.7 71.9
[0114] According to Table 6, the rebound modulus of the synergistic blending specimens of waste clay brick recycled powder and circulating fluidized bed solid sulfur ash is significantly better than that of the single blending specimens of waste clay brick recycled powder or circulating fluidized bed solid sulfur ash, and the rebound modulus of the synergistic blending specimens shows a trend of first rapid increase and then slow decrease with the increase of circulating fluidized bed solid sulfur ash dosage. It may be that the synergistic blending of waste clay brick recycled powder and circulating fluidized bed solid sulfur ash can stimulate each other's potential volcanic ash activity, so that the material undergoes hydration reaction and produces more hydration products and gel phase products that can support strength, making the internal structure of the mixture more compact, resulting in an increase in its rebound modulus. In addition, the minimum rebound modulus of the BF1 specimen is 62MPa, while the maximum rebound modulus of the BF4 specimen is 71.9MPa, further confirming that the synergistic ratio of the two will affect the degree of hydration.
[0115] 2.4 Shear strength analysis
[0116] Table 7: Shear strength analysis results
[0117]
[0118] According to Table 7, the shear strength of the synergistic blending specimens of waste clay brick recycled powder and circulating fluidized bed solid sulfur ash is better than that of the single blending specimens of waste clay brick recycled powder or circulating fluidized bed solid sulfur ash, and the shear strength of the synergistic blending specimens shows a trend of first rapid increase and then slow decrease with the increase of solid sulfur ash content. It may be that the synergistic blending of waste clay brick recycled powder and circulating fluidized bed solid sulfur ash within a reasonable range can improve the filling rate of fine particles to coarse particles' large pores, so that the particles generate a larger bite force through embedding and interlocking, thereby showing an increase in the shear strength of the specimens.
[0119] 2.5 Consolidation test analysis, results are shown in Figure 1 .in, Figure 1 The changes in compression coefficient and compression modulus of specimens BF1-BF4.
[0120] according to Figure 1 It can be seen that the compression coefficient of specimens BF1-BF4 shows a trend of first rapidly decreasing and then slowly increasing with the increase of circulating fluidized bed solid sulfur ash content, and the compression coefficient is between 0.1-0.5MPa. -1 Among them, the minimum compression coefficient of specimen BF4 is 0.12MPa. -1 At the same time, the compression modulus of specimens BF1-BF4 showed a trend of first increasing rapidly and then decreasing slowly with the increase of the fixed sulfur ash content. The compression modulus of specimen BF4 reached a maximum value of 15.43MPa. This may be because the waste clay brick recycled powder and the circulating fluidized bed fixed sulfur ash can synergistically produce more hydration products within a suitable range, which increases the solidification degree of the soil structure and causes the increase of the compression modulus.
[0121] 3. Shrinkage performance
[0122] When using roadbed backfill materials for road construction, they should not only have good mechanical properties, but also have good shrinkage properties to reduce cracks caused by drying shrinkage. Figure 2 The graph shows the change of water loss rate and shrinkage strain of specimens BF1-BF4 with curing age.
[0123] according to Figure 2As shown in (a), the water loss rate of specimens BF1-BF4 changes with the curing age in basically the same way, that is, as the curing age increases, the water loss rate gradually increases. Among them, within the 7d age, the water loss rate of specimens BF1-BF4 increases relatively slowly; within the 7d-28d age, the water loss rate of specimen BF4 increases relatively quickly, and the water loss rate of specimen BF4 is significantly higher than that of specimen BF1 in the later stage of curing. The reason may be that the synergistic blending of waste clay brick recycled powder and circulating fluidized bed fixed sulfur ash can significantly improve the density of the mixture, and the increase in density will reduce the pores between the mixture to reduce the water absorption rate. Therefore, the water loss rate can be increased by adjusting the synergistic ratio of waste clay brick recycled powder and circulating fluidized bed fixed sulfur ash to ensure stable performance.
[0124] according to Figure 2 As shown in (b), with the increase of age, the shrinkage strain of specimens BF1-BF4 shows a significant increasing trend. Among them, in the early stage of curing, specimens BF1-BF4 all show relatively small shrinkage strain; in the later stage of curing, the shrinkage strain of specimens BF1-BF4 changes more regularly, and its growth rate gradually accelerates, indicating that the shrinkage phenomenon of the soil roadbed filler modified by waste clay brick recycled powder and circulating fluidized bed solid sulfur ash is mainly concentrated in the later stage of curing age. According to the shrinkage mechanism, the loss of water in the macropores will not significantly cause the shrinkage of the mixture, so in the initial stage, the shrinkage phenomenon is relatively mild. However, with the continuous decrease of moisture content, capillary action, adsorption water effect and interlayer water effect gradually dominate the soil filler, which has a significant impact on the shrinkage performance of the soil filler, thereby significantly accelerating the growth rate of the shrinkage strain of the specimens.
[0125] 4. Microscopic analysis of gel phase products
[0126] In order to illustrate that the synergistic blending of waste clay brick recycled powder and circulating fluidized bed sulfur-fixing ash can generate a gel phase product, this paper mixed the waste clay brick recycled powder with the circulating fluidized bed sulfur-fixing ash, added water (water-cement ratio of 0.4) to prepare a slurry test block, and then carried out the following test.
[0127] 4.1 Mineral phase composition, the results are shown in Figure 3 .in, Figure 3 These are the XRD diagrams of the mineral phases of the hydration products of the waste clay brick recycled powder and circulating fluidized bed sulfur-fixing ash synergistic slurry test blocks at the ages of 3d and 28d respectively.
[0128] according to Figure 3It can be seen that in addition to the original quartz (SiO2) and albite (Na2O·Al2O3·6SiO2) mineral phases in the recycled powder of waste clay bricks and the solid sulfur ash phase of the circulating fluidized bed, calcium vanadium (3CaO·Al2O3·3CaSO4·32H2O) and calcite (CaCO3) were found in the clean slurry test blocks after 3d and 28d of curing, and the diffraction peak of calcium vanadium was clearly enhanced with the increase of the solid sulfur ash content of the circulating fluidized bed. During the hydration process from 3d to 28d, the diffraction peak of Ca(OH)2 partially weakened or disappeared, and the diffraction peak of CaCO3 was enhanced. This is the result of the reaction of Ca(OH)2 with CO2 in the air to form calcite CaCO3.
[0129] 4.2 Microscopic morphology, the results are Figure 4 As shown. Among them, Figure 4 These are the microscopic morphologies of the waste clay brick recycled powder and circulating fluidized bed sulfur-fixed ash synergistic slurry test blocks after hydration for 3d and 28d respectively.
[0130] according to Figure 4 It can be seen that when the waste clay brick recycled powder and circulating fluidized bed solid sulfur ash synergistic slurry test block was hydrated for 3 days, some needle-rod-shaped ettringite was generated on the surface of the raw material particles, but due to the incomplete hydration reaction, the amount of needle-rod-shaped ettringite produced was relatively small. Due to the presence of a small amount of ettringite and flaky CSH gel on the surface of the raw material particles, the brick powder and solid sulfur ash particles and hydration products were more closely connected, providing strength support in the early stage; and when the waste clay brick recycled powder and circulating fluidized bed solid sulfur ash synergistic slurry test block was hydrated for 28 days, the original raw material particles were greatly reduced, the hydration reaction between the waste clay brick recycled powder and the circulating fluidized bed solid sulfur ash and the volcanic ash reaction were complete, and a large amount of needle-rod-shaped ettringite was generated on the surface of the raw material particles, making the hydration products more closely connected, providing strength support in the later stage. Specifically, the early reaction of the recycled powder of waste clay bricks and the circulating fluidized bed solid sulfur ash was incomplete, resulting in low early mechanical strength. However, as the curing age increased, the volcanic ash reaction of the recycled powder of waste clay bricks and the circulating fluidized bed solid sulfur ash mixture intensified, and the amount of calcium aluminate generated increased, which accelerated the growth rate of mechanical strength in the later period. At the same time, by comparing BF4-a3-3d with BF4-b3-3d, it was found that the hydration reaction in the early stage of curing was incomplete, resulting in less AFt crystals, sparse distribution, and more holes. As the curing age increased, BF4-b3-3d generated more rod-shaped Aft crystals, and when distributed, they were mostly gathered together to form a relatively dense structure. The porosity inside the test block was greatly reduced, the density increased, and a large number of Aft crystals and a small number of holes were staggered, which was also the reason for the rapid growth of strength in the later period.
[0131] The various embodiments in this specification are described in a progressive manner, and the same or similar parts between the various embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.
[0132] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit the present application. Although the present application has been described in detail with reference to the aforementioned embodiments, a person of ordinary skill in the art should understand that the technical solutions recorded in the aforementioned embodiments may still be modified, or some or all of the technical features therein may be replaced by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the present application.
Claims
1. A composite solid waste and soil roadbed filler, characterized in that: Its raw materials include: Coarse-grained soil 60wt%; 8-15wt% recycled powder from waste clay bricks; and Circulating fluidized bed sulfur-fixing ash 25-32wt%.
2. The composite solid waste combined with soil roadbed filler according to claim 1 is characterized in that: Its raw materials include: 60wt% coarse-grained soil, 8wt% recycled powder from discarded clay bricks and 32wt% circulating fluidized bed sulfur-fixing ash; or, 60wt% coarse-grained soil, 10wt% recycled powder from discarded clay bricks and 30wt% circulating fluidized bed sulfur-fixing ash; or, 60wt% of coarse-grained soil, 13.3wt% of recycled powder from discarded clay bricks and 26.7wt% of circulating fluidized bed sulfur-fixing ash.
3. The composite solid waste combined with soil roadbed filler according to claim 1 or 2, characterized in that: The chemical composition of the waste clay brick recycled powder includes SiO2, CaO and Al2O3, and the sum of the masses of the SiO2, CaO and Al2O3 is 84.35% and above of all its chemical compositions.
4. The composite solid waste combined with soil roadbed filler according to claim 3 is characterized in that: The average particle size of the waste clay brick recycled powder is 17.74 μm.
5. The composite solid waste combined with soil roadbed filler according to claim 1 or 2, characterized in that: The chemical composition of the circulating fluidized bed desulfurization ash includes SiO2, CaO and Al2O3, and the sum of the masses of SiO2, CaO and Al2O3 is 83.89% and above of all its chemical compositions, and the mass of CaO is 10% and above of all its chemical compositions.
6. The composite solid waste combined with soil roadbed filler according to claim 5 is characterized in that: The average particle size of the circulating fluidized bed sulfur-fixing ash is 15.67 μm.
7. A method for preparing the composite solid waste and soil roadbed filler according to any one of claims 1 to 6, characterized in that: Include: The step of mixing the raw material components; and, adding water to the mixture obtained in the previous step and sealing and placing the mixture.
8. The preparation method according to claim 7, characterized in that: The amount of water added to the mixture is 16.3-21.3% of its weight.
9. Use of the composite solid waste according to any one of claims 1 to 6 in conjunction with soil roadbed fillers in backfilling construction of roadbed earth.
10. The use according to claim 9, characterized in that: During the backfill construction, the compaction degree is 96-98%.